2021
DOI: 10.3390/ijms221810178
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Serotonin 5-HT6 Receptor Constitutive Activity Alleviates Cognitive Deficits in a Preclinical Model of Neurofibromatosis Type 1

Abstract: Neurofibromatosis type 1 (NF1) is a common inherited disorder caused by mutations of the NF1 gene that encodes the Ras-GTPase activating protein neurofibromin, leading to overactivation of Ras-dependent signaling pathways such as the mTOR pathway. It is often characterized by a broad range of cognitive symptoms that are currently untreated. The serotonin 5-HT6 receptor is a potentially relevant target in view of its ability to associate with neurofibromin and to engage the mTOR pathway to compromise cognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…An important feature of the 5-HT 6 R is its high level of ligand-independent constitutive activity, which corresponds to the ability of a receptor to be active even in the absence of an agonist [10]. The role of 5-HT 6 R constitutive activity at canonical Gs signaling and non-canonical signaling has been described in various pathophysiological conditions [11][12][13][14][15]. Consistent with those findings, the development of 5-HT 6 R ligands acting as inverse agonists and/or neutral antagonists at the different 5-HT 6 R-operated signaling pathways is of utmost interest to decipher the cellular mechanism(s) under the control of the various 5-HT 6 R signal transduction mechanisms and of constitutive vs. agonist-dependent receptor activation.…”
Section: Introductionmentioning
confidence: 99%
“…An important feature of the 5-HT 6 R is its high level of ligand-independent constitutive activity, which corresponds to the ability of a receptor to be active even in the absence of an agonist [10]. The role of 5-HT 6 R constitutive activity at canonical Gs signaling and non-canonical signaling has been described in various pathophysiological conditions [11][12][13][14][15]. Consistent with those findings, the development of 5-HT 6 R ligands acting as inverse agonists and/or neutral antagonists at the different 5-HT 6 R-operated signaling pathways is of utmost interest to decipher the cellular mechanism(s) under the control of the various 5-HT 6 R signal transduction mechanisms and of constitutive vs. agonist-dependent receptor activation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous 5-HT receptors participate in cognitive processes and alteration of their activities might sustain cognitive deficits. Doucet et al reported strong evidence for the aberrant constitutive activity of 5-HT 6 receptors in a mouse model of neurofibromatosis type 1 (NF1), the nf1+/− mice [6]. This model resumes some of the cognitive deficits of the human disease.…”
mentioning
confidence: 99%